Eu escrivão a escrevi: análise das partículas discursivas jurídicas de um processo criminal do século XIX, à luz da linguística textual de base Coseriana - Bicalho, Márcia Amélia de Oliveira (2013)
The current doctoral work presents an analysis of the legal discursive particles which represent an aspect of truth in a criminal lawsuit from the 19th century in the city of Pombal Paraíba. In order to accomplish this intent, the work has been pedagogically divided into four chapters: a brief historical report regarding the Brazilian punitive process, the hermeneutics of the text based on Coşeriu s writings and its applicability in legal texts, the characterization of the legal procedural genres and the analysis of the legal discursive particles. The theoretical grounding is interdisciplinary, involving the Textual Linguistics based on Coşeriu s writings, Theory of Discursive Traditions, Social History of Language and Texts History, notably within the legal field. Amongst the consulted authors we can include Pierangelli (2007), Costa and Lemes (2011), Cristiani (2007), Coseriu (1977, 1978, 1979,1980, 2007, 2010), Fonseca (2003), Marcuschi (2003, 2012), Kabatek (2006), Koch (2006, 2007), Oesterreicher (1996, 2006), among others. The case that constitutes the corpus of the present work is presented in a single volume, being consisted of approximately sixty-one pages (front and back) handwritten with a total number of three hundred and ninety procedural documents. After the transcription of the corpus, we have mapped out the occurrences of the legal discursive particles and analyzed their function in the text, and extended the concept given by Eugenio Coşeriu regarding the discursive particles, thus, dividing them into three categories: initiating legal particles, legal particles of passage and finalizing legal particles. The results presented ratify the hypothesis that the legal discursive particles, used by Registrars, recaptures the times from the consolidation of genuinely Brazilian criminal laws, therefore, they are legal discursive traditions. We conclude this work by demonstrating that the discursive particles are used by the Registrar in order to orientate the reading and present their public authenticity, that is, the veracity of what was, written or rewritten by them within the legal discursive tradition.